African Improved Foods Investments - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
AIF is a public-private partnership involving DSM, and partners, based in Rwanda, but now entering into the Ethiopian and Kenyan market with projected $130M-205M in investment.